Contextual geometry teaching module: Innovation in developing practical learning materials for junior high school - Nurul Izzah; Nuralam Syamsuddin (State Islamic University of North Sumatra, 2025)
A teaching module serves as a structured learning tool aligned with the Merdeka Curriculum, designed to meet established competency standards. However, a mathematics teacher in Banda Aceh reported the absence of a curriculum-compliant teaching module specifically addressing triangle-related topics. This study aims to develop a practical and pedagogically appropriate teaching module guided by the principles of the Merdeka Curriculum. Given the nature of data collection, this research adopts a research and development (R&D) approach, employing the ADDIE model for systematic module development. Data were gathered through validation and practicality questionnaires, evaluated by subject matter experts, material experts, and teachers. The findings indicate that the teaching module demonstrates high validity, receiving scores of 95.00% from subject matter experts and 92.13% from material experts. In terms of practicality, the module also achieved strong ratings, with 88.16% from practitioners and 87.74% from students. Consequently, the teaching module is valid, practical, and suitable for implementation in classroom settings, warranting further trials and application in educational practice.